Bordetella pertussis attachment to respiratory epithelial cells can be impaired by fimbriae-specific antibodies - Rodríguez, María Eugenia (2006)
Bordetella pertussis attachment to host cells is a crucial step in colonization. In this study, we investigated the specificity of antibodies, induced either by vaccination or infection, capable of reducing bacterial adherence to respiratory epithelial cells. Both sera and purified anti-B. pertussis IgG or IgA fractions efficiently reduced attachment. This effect was found to be mediated mainly by fimbriae-specific antibodies. Antibodies with other specificities did not significantly interfere in the interaction of B. pertussis with respiratory epithelial cells, with the exception of antifilamentous hemaglutinin antibodies, which reduced bacterial attachment. However, this effect was smaller in magnitude than that observed in the presence of fimbriae-specific antibodies. The strong agglutinating activity of antifimbriae antibodies seems to be involved in this phenomenon.